From dynamism to dormancy: The jewellery industry in Johannesburg: 1925-2003 - Da Silva, Maria do Rosário Pinto Pereira (My University, 2008)
This study investigates the jewellery industry in South Africa from about the 1920s when the industry operated as a cluster in Johannesburg, to the more contemporary period of 2003. The industrial cluster approach to industrialisation forms the theoretical background for discussing the evolution of the jewellery cluster in this period. Various factors or “turning points” influenced the course of the cluster’s development and ultimately culminated in the demise of the jewellery cluster in Johannesburg. The study pays specific attention to the role of government in first resisting and then promoting the growth of jewellery manufacturing in South Africa. In recent years the jewellery industry has been the focus of both government and private sector initiatives to enhance its competitiveness globally. The result of these initiatives is discussed in the context of the internal and external constraints that affected the industry in the past and continue to play a role in the present.
Keywords: jewellery; industrial cluster; manufacturing; industry competitiveness